Exercise intensity and perceived exertion in adolescent boys. - Eston, R G (1986)
The rating of perceived exertion (RPE) was assessed at power outputs (PO) corresponding to 30%, 60% and 90% of predicted maximal oxygen uptake (VO2 max) on a cycle ergometer in 30 adolescent schoolboys (age range 15-17 years). Analysis of correlations (r) for heart rate (HR):PO (r = 0.74 p less than 0.01) and rating of perceived exertion (RPE): HR (r = 0.74 p less than 0.01) were similar to values drawn from adult samples. It was concluded that there is a close relationship between RPE, HR and relative exercise intensity in adolescent schoolboys.